Numerical Analysis and Optimization of a Hybrid Layer Structure for Triplet–Triplet Fusion Mechanism in Organic Light‐Emitting Diodes. Issue 2 (4th December 2022) - Huang, Jun‐Yu; Hung, Hsiao‐Chun; Hsu, Kung‐Chi; Chen, Chia‐Hsun; Lee, Pei‐Hsi; Lin, Hung‐Yi; Lin, Bo‐Yen; Leung, Man‐kit; Chiu, Tien‐Lung; Lee, Jiun‐Haw; Friend, Richard H.; Wu, Yuh‐Renn
Abstract: In this study, a steady state and time‐dependent exciton diffusion model including singlet and triplet excitons coupled with a modified Poisson and drift‐diffusion solver to explain the mechanism of hyper triplet–triplet fusion (TTF) organic light‐emitting diodes (OLEDs) is developed. Using this modified simulator, various characteristics of OLEDs, including the current‐voltage curve, internal quantum efficiency, transient spectrum, and electric profile are demonstrated. This solver can also be used to explain the mechanism of hyper‐TTF‐OLEDs and analyze the loss from different exciton mechanisms. Furthermore, we perform additional optimization of hyper‐TTF‐OLEDs that increases the internal quantum efficiency by ≈33% (from 29% to 40%). Abstract : In this work, a time ‐dependent exciton diffusion solver coupled with Poisson and drift‐diffusion solver for triplet‐triplet fusion (TTF) organic light‐emitting diodes (OLEDs) is developed to demonstrate the mechanism of TTF‐ and hyper‐TTF‐OLEDs. The loss mechanism of hyper TTF‐OLED is investigated, and optimized interrnal quantum efficiency can be improved from 29% to 40%.